Kategori Pasien Gangguan Jiwa Berdasarkan Triage Di Instalasi Gawat Darurat Rumah Sakit Jiwa Daerah Surakarta - Ardiyanti, Dhiny; , Arum Pratiwi, S.Kp., M.Kes (2016)
MENTAL DISORDERS BY CATEGORY OF PATIENT TRIAGE INSTALLATION IN EMERGENCY HOSPITAL REGIONAL MENTAL SURAKARTA By: Dhiny Ardiyanti Triage was a classification step of the patient's condition based on the gravity of the patient. This stage was very important to determine the type of action and the supplies required in the treatment of mental patients further. This study aims to determined the category of mental patients by triage in the emergency departement of Psychiatric Hospital Surakarta. This descriptive quantitative with cross sectional approach. The population of the study was patients who come to the emergency room of Mental Hospital of Surakarta. The sample of the study was 69 respondent with mental heath disorder. Sample technique used accidental sampling. Ilness data was collected using a checklist and then was analyzed using descriptive test. The results of the study regained acuty of mental patients that came into the emergency room Surakarta RSJD showed the lowest score with patient conditoin was 8 it means non-urgent, the highest score of 72 it means immediate, an average of 37.9, median 40, mode 40, and standard deviation of 15.9. The Conclusion on average the patients admitted to the emergency room of hospital regional mental Surakarta in conditions of semi-urgent. Keywords: triage, patient category, mental illness patients